2012
DOI: 10.1128/aem.07621-11
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Staphylolytic Activity of the Staphylococcus aureus Bacteriophage vB_SauS-phiIPLA88 HydH5 Virion-Associated Peptidoglycan Hydrolase: Fusions, Deletions, and Synergy with LysH5

Abstract: ABSTRACTVirion-associated peptidoglycan hydrolases have potential as antimicrobial agents due to their ability to lyse Gram-positive bacteria on contact. In this work, our aim was to improve the lytic activity of HydH5, a virion-associated peptidoglycan hydrolase from theStaphylococcus aureusbacteriophage vB_SauS-phiIPLA88. Full-length HydH5 and two truncated derivatives containing only the CHAP (cysteine, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 46 publications
0
75
1
Order By: Relevance
“…These enzyme pairs together were more efficient at degrading staphylococcal peptidoglycan than individually. 104 Similarly, this domain swapping approach has also proven to be useful for the improvement of lytic activity of the putative VAPGH within phage K open reading frame 56. 105 N-terminus deletions of orf56 defined the coding region responsible for a small PGH (Lys16) that retained staphylolytic activity.…”
Section: Virion-associated Peptidoglycan Hydrolasesmentioning
confidence: 99%
“…These enzyme pairs together were more efficient at degrading staphylococcal peptidoglycan than individually. 104 Similarly, this domain swapping approach has also proven to be useful for the improvement of lytic activity of the putative VAPGH within phage K open reading frame 56. 105 N-terminus deletions of orf56 defined the coding region responsible for a small PGH (Lys16) that retained staphylolytic activity.…”
Section: Virion-associated Peptidoglycan Hydrolasesmentioning
confidence: 99%
“…However, no cell wall binding (CWB) domain could be identified in the amino acid sequence of HydH5. In a subsequent study, Rodríguez-Rubio et al (16) demonstrated that the activity of the protein HydH5 could be improved by fusing its CHAP domain to the CWB domain SH3b of lysostaphin. The resulting chimeric protein was designated CHAPSH3b and exhibited specific activity against staphylococci.…”
mentioning
confidence: 99%
“…Therefore, although TG1 lytic activity was moderate against staphylococci, further investigation is worthwhile. We previously reported that the fusion of a staphylococcal SH3b cell wall-binding domain to the HydH5 CHAP domain resulted in a 4.8-fold increase of its lytic activity (15). Furthermore, it is plausible to swap different catalytic domains by protein engineering, generating proteins with improved lytic activity (4,15).…”
mentioning
confidence: 99%
“…E. coli BL21(DE3)/pLysS was used in protein expression assays (19). Purification of TG1 (30.1 kDa) was performed by nickel-nitrilotriacetic acid (Ni-NTA) chromatography (15). Peptidoglycan cleavage site determination was carried out by reverse-phase high-performance liquid chromatography (HPLC) and mass spectrometry (MS) (2).…”
mentioning
confidence: 99%